Exploring the knowledge, awareness and practices of COVID-19 among dentists in Bangladesh: A Cross-sectional Investigation - Mohammad Tawfique Hossain Chowdhury; Ehsanul Hoque Apu; Sujan Kanti Nath; Ashek Elahi Noor; Clopa Pina Podder; Ilias Mahmud; Russell Kabir (Universidad de Concepción., 2021)
Background: COVID-19 pandemic has caused an unpre-cedented strike on humanity around the world . The scenario in Bangladesh is getting worse day by day, and every aspect of the society is observing its impact. Health care professionals are at a greater risk of contracting the disease while caring for patients. Objective: The research objective is to explore knowledge, awareness, and practices of registered dentists regarding COVID-19 epidemiology and transmission during the rapid outbreak of this highly contagious virus in Bangladesh. Material and Methods: A cross-sectional web-based survey was conducted among the dentists who were enrolled with their valid unique Bangladesh Medical and Dental Council (BMDC) registration number. A structured questionnaire was distributed among the dentists through different social media platforms. A total of 184 dentists participated in the survey between March and April 2020. Both descriptive analysis and multivariable logistic regression analysis was performed. Results: The dentists' mean age was 31.75 years, with a standard deviation of 6.5 years. About 29.3% of dentists completed their postgraduate qualification, and 76% of them were engaged in private practice at the time of data collection. Compared to the dentists with undergraduate education, the dentists with a postgraduate education are three times (OR=3.1, 95%CI 1.2-7.9 and over 5 times (OR=5.3, 95% CI: 1.2-23.3) more likely to have) better knowledge and practices toward COVID-19 respectively. Dentists aged 26-30 years are less likely to have good practices than the younger dentists (OR: .1; 95% CI: .01-.5). However, dentists with less than five years experience are 10.3 (1.6-68.9) times more likely to have good practices compared to the dentists with more experience. Conclusion: Majority of the dentists from Bangladesh have shown good knowledge, awareness, and practice regarding COVID-19. We recommend that the healthcare authorities, professional organizations, and hospitals coordinate, and conduct mandatory advanced infectious disease training for all the practicing dentists in the country.